(untitled) (Journal of Contemporary Studies, 2024)
The rise of China has seemingly brought it on a collision course with the preeminent power, The United States of America. This has convinced various states most notably India, Pakistan, Iran, and the Gulf countries to re-orient their foreign policies. China’s investments through the Belt and Road Initiative (BRI), QUAD’s resurgence, Israel’s foray into the Arab countries, and persistent American support to enhance India’s stature at par with China, have pushed the Indian Ocean Region to be at the epicenter of all global rivalries. The presence of extra regional forces in Western Indian Ocean Region has ensured some semblance of stability in the region but it is the complex, interdependent relationship between strategically co-located states of Saudi Arabia, Iran, India, and Pakistan under the shadow of China-USA competition that is the objective of this study.